Critical Discourse Analysis of the Indonesian Government in the VUCA Era - Putranto, Algooth (UPT Publikasi Ilmiah UNISBA, 2024)
The rapid changes of the times affect various aspects of human life globally. This condition is considered part of the conditions that occur in the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA era). The VUCA era has also impacted people in Indonesia, especially in the economic sector, causing prices of basic necessities to keep rising. To manage the economic situation, the Indonesian government must adopt an effective public communication strategy to stabilize society. This research uses Stuart Hall's representation theory, which examines how language produces meaning in public communication. The aim is to analyze the government's communication strategy in responding to global economic and political uncertainty in the VUCA era. The study adopts a qualitative approach, utilizing critical discourse analysis by Norman Fairclough. The primary data comes from the Indonesian government's communications, specifically through the Presidential Secretariat's YouTube account, analyzing three selected videos. The findings indicate that President Joko Widodo's administration aims to shape public perception, reassuring citizens that the nation's economic uncertainty is manageable. This research highlights the importance of understanding the VUCA era and provides insights for the government to adopt appropriate communication strategies to guide public attitudes and behavior.